ChemInform Abstract: Synthesis of Novel Polysubstituted (2SR, 4RS)‐2‐Heteroaryltetrahydro‐1, 4‐epoxy‐1‐benzazepines and cis‐2‐Heteroaryl‐4‐hydroxytetrahydro‐1H‐1‐benzazepines as Antiparasitic Agents. Issue 11 (March 2015) - Blanco, Maria C.; Escobar, Patricia; Leal, Sandra M.; Bahsas, Ali; Cobo, Justo; Nogueras, Manuel; Palma, Alirio
Abstract Many of the new compounds (II), (III), (V), and (VI), synthesized via an intramolecular 1, 3‐dipolar cycloaddition of nitrones derived from O‐allyl‐N‐hetarylmethylanilines (I) or (IV), inhibit significantly the growth of extracellular forms of Trypanosoma cruzi and Leishmania infantum parasites without showing cytotoxicity on Vero and HTP‐1 cells.